Language arts - Kallos, Stephanie (Houghton Mifflin Harcourt, 2015)
Charles Morrow, a high school English teacher who finds it difficult to connect with his autistic son, his college-bound daughter, or his ex-wife, begins to rise out of the rut his life has fallen into with the help of an art student and an Italian-speaking nun.